Interobserver Agreement Rates on C-X-C Motif Chemokine Receptor 4–Directed Molecular Imaging and Therapy. (22nd June 2023) - Hartrampf, Philipp E.; Kosmala, Aleksander; Serfling, Sebastian E.; Bundschuh, Lena; Higuchi, Takahiro; Lapa, Constantin; Rowe, Steven P.; Matsusaka, Yohji; Weich, Alexander; Buck, Andreas K.; Bundschuh, Ralph A.; Werner, Rudolf A.
Abstract : Background: We aimed to evaluate the interobserver agreement rates in patients scanned with C-X-C motif chemokine receptor 4 (CXCR4)–directed PET/CT, including the rate of patients eligible for CXCR4-targeted radioligand therapy (RLT) based on scan results. Methods: Four independent observers reviewed 50 CXCR4-targeted [ 68 Ga]pentixafor PET/CT of patients with various solid cancers. On a visual level, the following items were assessed by each reader: overall scan impression, number of organ and lymph node (LN) metastases and number of affected organs and LN regions. For a quantitative investigation, readers had to choose a maximum of 3 target lesions, defined as largest in size and/or most intense uptake per organ compartment. Reference tissues were also quantified, including unaffected hepatic parenchyma and blood pool. Last, all observers had to decide whether patients were eligible for CXCR4-targeted RLT. Concordance rates were tested using intraclass correlation coefficients (ICCs). For interpretation, we applied the definition of Cicchetti (with 0.4–0.59 indicating fair; 0.6–0.74, good; 0.75–1, excellent agreement). Results: On a visual level, fair agreement was achieved for an overall scan impression (ICC, 0.58; 95% confidence interval, 0.45–0.71). Organ and LN involvement (ICC, ≥0.4) demonstrated fair, whereas CXCR4 density and number of LN and organ metastases showed good agreement rates (ICC, ≥0.65). Number of affected organs and affected LN areas, however, showed excellent concordance (ICC, ≥0.76). Quantification in LN and organ lesions also provided excellent agreement rates (ICC, ≥0.92), whereas quantified uptake in reference organs provided fair concordance (ICC, ≥0.54). Again, excellent agreement rates were observed when deciding on patients eligible for CXCR4-RLT (ICC, 0.91; 95% confidence interval, 0.85–0.95). Conclusions: In patients scanned with CXCR4-targeted PET/CT, we observed fair to excellent agreement rates for both molecular imaging and therapy parameters, thereby favoring a more widespread adoption of [ 68 Ga]pentixafor in the clinic.